Dynamics of the Development of the Salafiyah Movement in Kerinci, Jambi: A Study of Theological Roots and Social Impact - I, Martunus; Mirdad, Jamal; Putri, Auliana Nur (Sekolah Tinggi Agama Islam Syekh Abdur Rauf Aceh Singkil, Aceh, Indonesia, 2024)
The Salafiyah movement is part of the reformist movement in Islam which operates in the field of purifying Islamic teachings based on the Koran and the Hadith of the Prophet Muhammad. In accordance with what was done by the previous generation (Salafus saleh). In Kerinci the Salafi movement exists in a social context that has its own characteristics. The aim of this research was to look at the development and theological roots of Salafiyah as well as the social impact in Kerinci. formulation of the problem in this research: 1). What are the dynamics of the development of the Salafiyah movement in Kerinci. 2). How Salafi theological thought is explained in detail. 3) What is the social impact. This research method uses a qualitative method with a field study and literature approach. The results of the research explain that the Salafiyah movement entered Kerinci in the 18th century, brought by traders and ulama from Minang Kabau and ulama from Kerinci. The development of the Salafi movement was more rapid after the reformation. While the theological roots of Salafiah are focused on purifying Islamic teachings, inviting people to return to the sources of Islamic teachings, the Koran and Hadith, elements of superstition, heresy and Khurafat in worship are not permitted. [Gerakan salafiyah merupakan bagian dari gerakan reformis dalam Islam yang bergerak dibidang pemurnian ajaran Islam yang bersumber Al-Qur’an dan Hadist Nabi Muhammad Saw. Sesuai dengan yang dilakukan oleh senerasi terdahulu (Salafus saleh). Di Kerinci gerakan Salafiah hadir dalam konteks sosial kemasyarakatan yang mempunyai krakteristik tersendiri. Tujuan dilakukan penelitian ini untuk melihat perkembangan dan akar teolologis salafiyah serta dampak sosial di Kerinci. rumusan masalah dalam penelitian ini: 1). Bagaimana dinamika perkembangan gerakan Salafiyah di Kerinci. 2). Bagaimana pemikiran teologis Salafiah di kerinci. 3) Bagaimana dampak sosial. Metode penelitian ini menggunakan, metode kualitatif dengan pendekatan studi lapangan dan kepustakaan. Hasil dari penelitian menjelaskan aliran Salafiyah masuk di Kerinci pada abad ke 18 yang dibawa oleh pedagang dan para ulama dari Minang Kabau serta ulama dari Kerinci. Perkembangan gerakan Salafiah lebih pesatnya pasca repormasi. Sedangkan akar teologis Salafiah terfokus pada pemurnian ajaran Islam mengajak masyarakat kembali kepada sumber ajaran Islam al-Qur’an dan hadis, tidak dibenarkan adanya unsur takhayul, bid’ah dan Khurafat dalam ibadah].